A contractor selection model for gas and oil industries in safety approach using ANP-DEMATEL in grey environment. Issue 1 (2nd January 2017) - Gharedaghi, Gholamreza; Omidvari, Manouchehr
Abstract: The specialisation of the activities of different industrial sectors is one of the characteristics of today's business market. The outsourcing of some activities of an organization as a project and contractor selection is one of the major concerns of managers in industries such as oil industry. Assessment of contractors based on specified criteria and ultimately selecting an eligible contractor retaining the organisational resources is a major challenge. Due to the risks and conditions of the oil industry, one of the main criteria of contractor selection is safety, which is today considered by several executives. This study aimed to provide a model for contractor selection in the oil industry with a safety approach using a hybrid Analytic Network Process - Decision Making Trial and Evaluation Laboratory Model (ANP-DEMATEL) and grey relational analysis in order to minimise the impact of appraiser's qualitative personal judgment on the assessment process and contractor selection by establishing a conceptual structure. The results indicated that the most important safety criterion of contractor selection in the oil industry was 'safety records and safety investments'. This represented the industry's risks and the impact of safety training and safety investment on the performance of other sectors and overall organisation.